Perancangan Aplikasi Menentukan Harga Jual Tanaman Berbasis Web Mobile Menggunakan Metode Full Costing - Rusdiyanto, Rusdiyanto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Technology greatly affects the progress of the business, either individually, government agencies, or private sector. The development of information has a very important role in an effort to create progress in all areas intended for human benefit in general. Information systems are also an important part of the company in improving productivity. Rader Flower is a shop that is engaged in the sale of crops. In producing all of its products Rader Flower provides local raw materials and manufacturing is self-made. The problems faced by Rader Flower are determining the underlying price of the production, because currently the calculation of the cost of the product produced by the store is a calculation based solely on store policy and adjust and follow the price Market alone without calculating correctly and the specific working capital for a product, so it is very difficult for the shop Rader Flower to set the selling price of the production and of course this can affect in obtaining profits Or profit on the store. In this research, the design was built to determine the selling price of mobile web based plants using the full costing method. Can be concluded that this application can determine the price of plant sales at the shop Rader Flower.